Evidence for alpha-synuclein aggregation in older individuals with hyposmia: a cross-sectional studyResearch in context - Kenneth Marek; David S. Russell; Luis Concha-Marambio; Seung Ho Choi; Danna Jennings; Michael C. Brumm; Christopher S. Coffey; Ethan Brown; John Seibyl; Matthew Stern; Claudio Soto; Andrew Siderowf (EBioMedicine)
Summary: Background: Synuclein pathology in neurodegenerative diseases, such as Parkinson’s disease (PD) and Dementia with Lewy bodies (DLB), begins years before motor or cognitive symptoms arise. Alpha-Synuclein seed amplification assays (α-syn SAA) may detect aggregated synuclein before symptoms occur. Methods: Data from the Parkinson Associated Risk Syndrome Study (PARS) have shown that individuals with hyposmia, without motor or cognitive symptoms, are enriched for dopamine transporter imaging (DAT) deficit and are at high risk to develop clinical parkinsonism or related synucleinopathies. α-syn aggregates in CSF were measured in 100 PARS participants using α-syn SAA. Findings: CSF α-syn SAA was positive in 48% (34/71) of hyposmic compared to 4% (1/25) of normosmic PARS participants (relative risk, 11.97; 95% CI, 1.73–82.95). Among α-syn SAA positive hyposmics 65% remained without a DAT deficit for up to four years follow-up. α-syn SAA positive hyposmics were at higher risk of having DAT deficit (12 of 34) compared to α-syn SAA negative hyposmics (4 of 37; relative risk, 3.26; 95% CI, 1.16–9.16), and 7 of 12 α-syn SAA positive hyposmics with DAT deficit developed symptoms consistent with synucleinopathy. Interpretation: Approximately fifty percent of PARS participants with hyposmia, easily detected using simple, widely available tests, have synuclein pathology detected by α-syn SAA. Approximately, one third (12 of 34) α-syn SAA positive hyposmic individuals also demonstrate DAT deficit. This study suggests a framework to investigate screening paradigms for synuclein pathology that could lead to design of therapeutic prevention studies in individuals without symptoms. Funding: The study was funded by the U.S. Department of Defense, the Helen Graham Foundation and the Michael J. Fox Foundation for Parkinson's Research.